The Pregnancy Heart Team Approach for the Adult with Hypertrophic Cardiomyopathy and Severe Left Ventricular Outflow Tract Obstruction. Issue 1 (9th January 2021) - Huang, Sihong; Samuel, Bennett P.; Cordoba, Marcos; Romero, Vivian C.; Chalifoux, Laurie; Fermin, David R.; Cook, Stephen C.
Abstract : Abstract: Hypertrophic cardiomyopathy (HCM), the most common single-gene cardiovascular disease, is associated with increased risk for arrhythmias, heart failure, and sudden cardiac death. The hemodynamic changes known to occur during pregnancy can exacerbate heart failure and arrhythmias in women with HCM. We present a 30-year-old woman with HCM to illustrate the benefits of multidisciplinary team management of severe left ventricular outflow tract obstruction (peak gradient >100 mmHg) for optimal maternal and fetal outcomes.